الولاية العامة للمرأة في الفقه الإسلامي : دراسة تحليلية بالإحالة إلى الواقع الماليزي - Asar bin Abdul Karim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to discuss the issues on women's positions in public office positions in Islamic jurisprudence. The issue is a controversial subject matter in Muslim community, including Malaysian Muslim community which is the scope of study for this research. It could be generalized that the Muslim jurists' views on this issue are divided in three directions. There is a group of jurists which prevents it, some of it allow it only in necessity basis. There is another group which holds it as an absolute permissible, while the last group allows it only for specific fields. This study addresses the issue in five chapters. The first chapter is the introductory chapter; the second has the definitions and types of public offices, and presents the situations that allow the positions for women. The third chapter discusses the views of Muslim scholars; the fourth discusses the eligibility of women to hold public office positions in light of contemporary developments. The final chapter describes the extent of approval norm among Malaysian Muslim community on women working outside home as well as holding public office positions. The research used several notable methods, namely the inductive method, analytical method, comparative method, critical method and field method to collect the views from the Malaysian Muslim community. The findings reveal a number of dimensions of rules for women to hold public office positions. The most important finding is the permissibility of women to hold public office positions based on Shari'ah guidelines – except for the state presidency and alike, the positions that contradict women's nature and the nature of the positions. A woman also is not allowed to be an imam for prayer or to call adhan for men. These types of public office positions are solely designated for men. In actuality, the whole issue is related to the legal maxim: giving job to the right person. The findings are the average views gathered; hence, by Allah's will, they contribute to the elimination or lesser disputes about the issue. Allah knows the best.